Food habits of common carp (Cyprinus carpio L.,1758) in Main Outfall Drain ,Al-Nassiriya, Iraq. - Al-Awady, Afrah A. Maktoof (University of Thi-Qar Journal of Science, 2013)
The, alimentary canal contents of 360 common carp (Cyprinus carpio) caught from MOD betweenJanuary 2010 to December 2010 were examined. The phytoplankton, zooplanktons, detritus, diatoms, insects, unidentified digestive foods were identified in the alimentary canal of fish.The results of analysis showed that the C.carpio, was omnivorous. Food contents consist of plant. The species of fish tend to consumed more plant origin food. The aquatic plants and tissues were the main part of the food followed by chlorophyta and cyanophyta. The results revealed that the species obtained or fallen their food items from the bottom or the near of it.